Penerapan Digital Marketing Sebagai Strategi Pemasaran UMKM (Studi Kasus Pada UMKM Dapoer Cesky) - Yosia Triputra Rahardjo; Devi Putri Pratama; Anggita Dini Fitria; Dita Puspita Septyaningrum; Alief Abdullah Faqih (Politeknik Kampar, 2023)
The rapid advancement of information technology has significantly changed the scope of the marketing world. Marketing communication methods that were previously very conventional and traditional have now been integrated into the digital world. Digital marketing is a general term used to describe marketing activities that utilize digital technology. Digital marketing consists of interactive and engaging elements that facilitate communication between producers, traders and consumers. Here will also be carried out the stages of observation, interviews, implementation, and implementation. Dapoer Cesky, which has been active in the food and pastry industry since 2018, understands very little about digital marketing. In addition, partners are given socialization on how to create accounts on digital media such as Google Business and Instagram and how to manage them so that their reach is wider. Through the efforts made, digital marketing has a major influence on growth and development, especially Dapoer Cesky, which is starting to grow its name and business. With the strategy implemented, it is able to encourage economic growth for the Dapoer Cesky business actor to become a superior value and differentiator from other businesses amidst the large number of businesses engaged in the same business sector.